Pemanfaatan Objek 3D Printing Sebagai Pengembangan Media Pembelajaran Bangun Ruang Berbasis Arduino Untuk Siswa Penyandang Tunanetra - Arianti Arianti; Badar Alpian; Mochamad Ghazali Al Fharezi; M. Apriyadi Tri Putra; Priti Priti; Rudi Hermawan (Lembaga Sosial Rumah Indonesia, 2023)
Mantera Media Development is a project aimed at creating effective learning materials for visually impaired students. These materials utilize 3D printing technology and are based on Arduino technology. The development process follows a Research and Development (R&D) methodology with a prototype model approach. This project was conducted at Sriwijaya University's Mechanical Engineering Education Laboratory. The validation results for the learning materials were impressive. Material validation using a Likert scale yielded a perfect score of 100%, indicating high appropriateness and validity. Media validation, assessed using Guttman theory, scored 91%, signifying the media's strong suitability and validity. As a result, these learning materials are considered highly feasible and ready for use in teaching build space concepts to visually impaired students. Mantera's development promises to address the challenges faced in learning space construction, potentially enhancing cognitive and tactile skills. Additionally, it introduces technology-packaged media to the educational landscape.